The Rights of Non-Muslims in an Islamic State - Rudi Rudi; Yaman Suryaman (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2020)
This article seeks to examine the position and rights of non-Muslim citizens in an Islamic country. The study results found that non-Muslims are seen as citizens by an Islamic state, even though they are not natives of that country. Islamic justice and the principle of equality in Islam require that Christians, Hindus, Buddhists, Melanesians, Turks, or Arabs be treated the same as other citizens in their own country. He is entitled to enjoy the same privileges as a citizen regardless of religious affiliation.